Media pelestarian budaya lokal di desa argosuko - sari, Desi lutfiyah (Maliki Interdisciplinary Journal, 2025)
Kuda lumping is one of the traditional Javanese performing arts that is rich in cultural, spiritual, and social values. In Argosuko Village, Poncokusumo District, Malang Regency, the Songgorejo kuda lumping continues to hold a special place in the hearts of the community. This performance is not merely a form of folk entertainment, but also serves as a means of preserving identity, strengthening solidarity, and creating economic opportunities. This article seeks to examine the role of kuda lumping as a medium for cultural preservation amid the increasingly strong currents of globalization. In Javanese tradition, kuda lumping is regarded as a symbol of strength, resilience, and the relationship between humans, nature, and the spiritual world. Accompanied by gamelan music and magical attractions, kuda lumping possesses a unique appeal. In Argosuko Village, its presence not only reinforces social cohesion but alscreates a space for intergenerational interaction. The older generation serves as guardians of tradition, while the younger generation becomes both successors and innovators in ensuring the continuity of this art form. This article employs a qualitative approach based on literature and socio-cultural analysis. The findings show that kuda lumping plays a multidimensional role: as cultural identity, a medium of traditional education, a spiritual space, a driver of the local economy, and a tradition facing the challenges of modernization. Therefore, the preservation of kuda lumping requires collaborative strategies involving the community, government, academics, and artists. In this way, the Songgorejo kuda lumping can continue to serve as a symbol of the sustainability of local culture that must be safeguarded and developed.